Dinamika Hubungan Antara Pengujian Undang-Undang dengan Pembentukan Undang-Undang - Utomo, Nurrahman Aji (Mahkamah Konstitusi Republik Indonesia, 2015)
The development and implementation of a relationship leading to the birth of anomalous friction decision Judicial review to collide against the lawmaking function. The absence of a follow-up mechanismÂ to cancel the decision of the norm, led toÂ Â the birth anomaly judgment. Friction Judicial Review with Law making Function was born in the form of vague and superficial to the lack of follow-up mechanisms. Efforts to reduce the friction between the two of them was done to achieve the ideal relationship between judicial review with lawmaking function.